Investigasi Dampak Shopping Motivation Pada Generasi Z Pengguna Smartphone Merek iPhone di Kota Samarinda - Anugrahni, Sisilia; Bharata, Wira; Arsyad, Annisa Wahyuni; Andriana, Ana Noor (Universitas Multi Data Palembang, 2024)
This study aims to determine whether utilitarian motivation and hedonic motivation can affect satisfaction which later leads to the loyalty attitude of generation Z iPhone brand smartphone users in Samarinda City. This research is a type of quantitative research with associative methods. The population in this study is generation Z who use iPhone smartphones in Samarinda City. The sample was obtained using accidental sampling technique and using data analysis techniques in the form of Structural Equation Modeling (SEM)-PLS method. Based on the results of the study, it shows that hedonic motivation has a significant effect on customer satisfaction and loyalty. While utilitarian motivation only has a significant effect on customer satisfaction, it has no significant effect on customer loyalty.